2021
DOI: 10.3390/medicina57111266
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Natural Products for Prevention of Acute Kidney Injury

Abstract: Background and Objectives: acute kidney injury (AKI), formerly called acute renal failure (ARF), is commonly defined as an abrupt decline in renal function, clinically manifesting as a reversible acute increase in nitrogen waste products—measured by blood urea nitrogen (BUN) and serum creatinine levels—over the course of hours to weeks. AKI occurs in about 20% of all hospitalized patients and is more common in the elderly. Therefore, it is necessary to prevent the occurrence of AKI, and to detect and treat ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 91 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…In line with the findings from clinical and animal studies, we observed that rats with ischemia-reperfusion had severely impaired kidney function and increased oxidative stress. Targeting oxidative stress is emerging as a promising strategy for the prevention and treatment of AKI and other diseases [ 14 , 18 , 44 ]. Folate (folic acid) is an essential micronutrient for DNA synthesis and one-carbon reactions in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with the findings from clinical and animal studies, we observed that rats with ischemia-reperfusion had severely impaired kidney function and increased oxidative stress. Targeting oxidative stress is emerging as a promising strategy for the prevention and treatment of AKI and other diseases [ 14 , 18 , 44 ]. Folate (folic acid) is an essential micronutrient for DNA synthesis and one-carbon reactions in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no standard pharmacological agents clinically approved to treat AKI effectively. Early detection and prevention are the key strategies for AKI management [ 14 , 15 ]. According to a commentary on the Kidney Disease: Improving Global Outcomes (KDIGO) clinical practice guidelines for AKI, the supply of adequate nutrients plays a vital role in reducing metabolic complications in AKI patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds recommended for kidney cancer were searched both in some databases such as NPACT (Naturally occurring Plant-based Anticancerous Compound-Activity-Target DataBase), CTD (The Comparative Toxicogenomics Database), and in the literature (Haque et al, 2017;Prša et al, 2020;Kang et al, 2021;Molaei et al, 2021;Wang et al, 2021). From the search, about five hundred natural compounds were found against kidney damage and cancer.…”
Section: Screening and Selection Of Natural Compounds For Kidney Cancermentioning
confidence: 99%
“…Plant-derived medicines have attracted considerable attention owing to their minimal side effects and cost-effectiveness. Many natural compounds, such as flavonoids, polyphenols, and terpenoids, are effective against AKI because of their anti-oxidative and anti-inflammatory effects [ 12 ]. However, it is not yet clear whether these natural compounds can be used as drugs or dietary supplements to prevent or treat AKI.…”
Section: Introductionmentioning
confidence: 99%